Applicant perceptions of selection procedures: The role of selection information, belief in tests, and comparative anxiety - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2003)
This study addresses the effects of the provision of information on the reliability and validity of selection procedures and the effects of test-taker attitudes (i.e., belief in tests and comparative anxiety) on fairness perceptions. Prior to an actual selection process, applicants (N = 118) were given either information about the reliability and validity of various selection procedures or no information. Next, they evaluated the fairness of eight selection procedures. No significant effect of selection information was found. Belief in tests had significant effects, with applicants high on test belief giving higher fairness ratings than applicants low on test belief. In addition, an interaction effect between test belief and selection procedure was found. For example, test belief had larger effects on fairness for structured interviews, personality inventories, and cognitive ability tests. No significant effect of comparative anxiety on fairness was found.